ChemInform Abstract: Rare‐Earth Manganese Arsenides RE4Mn2As5 (RE: La—Pr). Issue 23 (June 2015) - Tabassum, Danisa; Lin, Xinsong; Mar, Arthur
Abstract The title compounds are prepared from the elements in the presence of Ga flux (fused silica tubes, 800 °C for 3 d, 1050 °C for 2 d) and characterized by powder and single crystal XRD.